IN REACTIONS OF CONDENSED HETEROCYCLIC COMPOUNDS OF ZUCCHINI-FELDS - Тухсанов Феруз Садуллаевич; Орипов Эргаш Орипович; Хайдаров Гайрат Шойимович (Galaxy International Interdisciplinary Research Journal, 2023)
In an article from 2-aminobenzoic acid and pyrrolidone-2 in the presence of various substances,for example, PCl5, POCl 3, 2,3-trimethylene-3,4-dihydrobenzo[2,3-d]pyrimidin-4-one was synthesized. Its reduction reaction with NaBH 4 was carried out. The resulting 2,3- trimethylene-1,2,3,4-tetrahydrobenzo[2,3-d]pyrimidine-4-one - a three-component combination of carbonyl, amine and hydrophosphoryl compound leads to α-aminophosphonates, phosphoric acid-formaldehyde; Reactions with aldehydes in a three-component system have been studied.